SEROPREVALENCE OF TOXOPLASMA GONDII IN FEMALE LLAMAS OF THE CENTRAL HIGHLANDS OF PERU - Chang H., Katty (2009)
The objective of the study was to determine the seroprevalence of Toxoplasma gondii in female llamas of Corpacancha, Cuyo, and Santa Ana production units of the Cooperative Pachacutec, located in the district of Marcapomacocha, Junín. Blood samples (n = 249) were collected in January and February 2003 from animals more than one year of age. The immunofluorescence test (IFAT) was used for the detection of antibodies against T. gondii. The seroprevalence was moderate (13.7 ± 4.3%, 34/249). There was a greater risk of infection for llamas over 6 years and for those at Santa Ana and Corpacancha production units.